Kinerja Karyawan PT Umafindo Jepara Dipengaruhi Komitmen Organisasi Dan Motivasi Kerja - Safira, Wulan Aprilia Putri; Fuad, Eko Nur (Ecobuss, 2025)
This study aims to examine the mediation effect of organizational commitment on the relationship between motivation and employee performance. This study uses primary data obtained from the results of the questionnaire. The population of the study to be observed is all employees of PT. UMAFINDO totaling 50 employees. The sampling technique used in this study is the nonprobability sampling technique which is included in saturated sampling, so that all employees are sampled. The analysis technique used in this analysis is PLS-SEM (Partial Least Squares Structural Equation Modeling) and the tool used is SmartPLS 3. Empirical findings show that organizational commitment has a significant effect on employee performance. Work motivation does not affect employee performance. Work motivation has a significant effect on organizational commitment. Work motivation does not affect employee performance through organizational commitment.